Pinos transcorticais e gesso associados à aplicação local de plasma rico em plaquetas no tratamento de fratura do III metatarsiano em potro - Watanabe, Marcos Jun [UNESP]; Milluzi Yamada, Ana Lucia [UNESP]; Garcia Alves, Ana Liz [UNESP]; Alonso, Juliana de Moura [UNESP]; Barbosa, Roberta Galvano; Mantovani, Cristina de Faria [UNESP]; Hussni, Carlos Alberto [UNESP] (Universidade Federal de Santa Maria, 2015)
In horses less than one year of age fractures of the third metacarpal bone (McIII) or metatarsal bone III (MtIII) are mainly attributed to trauma. Open reduction and internal fixation are the most common treatment method. A Quarter Horse filly with three months of age, which weighed 150kg presented a diaphyseal multifragmentar wedge fracture of right MtIII which was treated with transcortical pins and cast, associated with intralesional application of platelet rich plasma (PRP). After two years of surgery, the animal initiated a training program for racing, and six months later, the patient ran its first official match. The choice of therapeutic methods for treating fractures in horses should be one that provides an earlier repair and minor possibility of complications. Thus, the therapy association which was adopted was considered favorable, since allowed full reestablishment of locomotion of the patient and made possible its return to race.

Em potros até um ano de idade, as fraturas do III osso metacarpiano (McIII) ou III metatarsiano (MtIII) são principalmente atribuídas ao trauma. A redução aberta e a imobilização do foco com implantes constituem o tratamento cirúrgico recomendado. Uma potra com três meses de idade e 150kg, da raça Quarto de Milha, que apresentava umafratura diafisária multifragmentar em cunha do MtIII direito foi submetida à osteossíntese através datransfixação externa e gesso, associada com a aplicação intralesional deplasma rico em plaquetas (PRP). Após dois anos do tratamento, o animal iniciou programa de treinamento para corrida e, após seis meses do treinamento, correu o primeiro páreo oficial. A escolha dos métodos terapêuticos para o tratamento de fraturas em equinos deve ser baseada naquela que promova reparação precoce e de melhor qualidade, com menores riscos de complicações. Sendo assim, a associação terapêutica adotada foi considerada favorável, já que possibilitou o completo reestabelecimento da locomoção da paciente, podendo inclusive competir na sua modalidade esportiva.
Transfixation pin cast associated with local platelet rich plasma for treatment of third metatarsal fracture in a filly
Keywords: Equine; Fracture; Osteosynthesis; Platelet rich plasma; Equino; Fratura; Osteossíntese; Plasma rico em plaquetas